(untitled) (Confluenţe Bibliologice, 2021)
Between 2015-2018, the USARB Scientific Library participated in the International Project "Library Network Support Services: modernising libraries in Armenia, Moldova and Belarus through library staff development and reforming libraries” [LNSS], co-funded by the Erasmus+ Programme of the European Union. It was an Institutional Capacity Building Project,one of the specific objectives being the increase of the visibility and the role of the library through the annual development of the National Awareness Day (NAD) in the society. Participants in this project were nine university libraries in Armenia, Belarus and the Republic of Moldova with the Scientific Library of the Academy of Public Administration in Chisinau and the Scientific Library of "Alecu Russo” Bălţi State University. Following the recommendations of the Project and the experiences of European libraries, librarians from the two nominated institutions, already for five consecutive years, are carrying out action programs to mark the National Library Awareness Day, an event coincides with Librarian Day in Moldova and World Book Day and Copyright. This paper reiterates the actions taken by the USARB Scientific Library dedicated to the National Library Awareness Day: celebration in the Government House of the Republic of Moldova, National Book Collection and Donation Campaign, Literary Characters Gala (Cosplay), organization of public debates, youth seminar researchers from the north of the country, Student Lecture - 2017, round table on access to education for young people with disabilities in Moldova with a focus on university education, thematic exhibitions, book caffe, Zig Zag Café, flash mobs, etc.